2021
DOI: 10.1002/advs.202103005
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Electrical Stimulation at Dorsal Root Ganglions Accelerates Osteoporotic Fracture Healing via Calcitonin Gene‐Related Peptide

Abstract: The neuronal engagement of the peripheral nerve system plays a crucial role in regulating fracture healing, but how to modulate the neuronal activity to enhance fracture healing remains unexploited. Here it is shown that electrical stimulation (ES) directly promotes the biosynthesis and release of calcitonin gene-related peptide (CGRP) by activating Ca 2+ /CaMKII/CREB signaling pathway and action potential, respectively. To accelerate rat femoral osteoporotic fracture healing which presents with decline of CGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 66 publications
0
49
0
Order By: Relevance
“…Bone fracture is one of the most common traumatic injuries [ 1 , 2 ]. By 2050, the annual number of fractures in China will reach 5.99 million which will cost $25.43 billion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone fracture is one of the most common traumatic injuries [ 1 , 2 ]. By 2050, the annual number of fractures in China will reach 5.99 million which will cost $25.43 billion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher activity was observed for cortical neurons in the presence of C-RB02 NPs with respect to cells in control conditions and cells exposed to RB02 NPs (Figure b). Electrical stimulation using electrodes can induce calcium signaling in cortical neurons, dorsal root ganglions, and even nonexcitable brain cells . Here, wireless electrical stimulation and intracellular calcium release is achieved by charged NPs.…”
Section: Resultsmentioning
confidence: 99%
“…In January 2022, Mi et al implanted electrodes into the dorsal root ganglia (DRG) at the L3 and L4 of the rat spine. They found that electrical stimulation of the DRG could activate the Ca 2+ /CaMKII/CREB signaling pathway and action potential, directly promoting the synthesis and release of CGRP, further inducing osteoporotic fracture healing and the formation of H-type blood vessels ( 20 ). Peripheral nerves can secrete neurotransmitters, neuropeptides, neurotrophic factors, among other signaling molecules, which can affect bone metabolism.…”
Section: Quaternary Regulation Theory Of Bone Metabolismmentioning
confidence: 99%